BUFFER ANALYSIS OF THE REACH OF PASSPORT ISSUING SERVICES USING GEOGRAPHIC INFORMATION SYSTEM (GIS) APPLICATIONS (CASE STUDY OF YOUR KUALANAN PASSPORT SERVICE UNIT) - Yusuf Junianto (Polteknik Imigrasi, 2020)
The government organizes public services in the immigration sector in terms of issuing passports through the Directorate General of Immigration which has the responsibility of carrying out immigration functions and determining service standards for each Technical Service Unit owned. In providing public services, the TPI Medan Special Class I Immigration Office is responsible for four districts and two cities covering Langkat Regency, Deli Serdang Regency, Serdang Bedagai Regency, Karo Regency, Medan City and Binjai City. With a large enough working area, it is necessary to establish an Office Work Unit or Passport Service Unit as an effective and efficient way to carry out immigration functions and to bring services closer to the public. The establishment of an Office Work Unit (UKK) and a Passport Service Unit (ULP) based on the workload of the Technical Implementing Unit is very broad so it is necessary to establish an Office Work Unit and Passport Service Unit to optimize immigration functions to the community. The aim is that every community can get the fulfillment of service needs in accordance with the laws and regulations governing the delivery of public services. In the framework of establishing an Office Work Unit (UKK) and Passport Service Unit (ULP), it is necessary to determine a strategic location and can be reached by the community so that it can achieve its maximum function. The Kualanamu Passport Service Unit is located in the Kualanamu Airport area, which is located in Beringin District. Therefore, this study aims to analyze strategic locations in determining the location of ULPs. In order to analyze the location and range of services, a spatial buffering analysis was carried out as well as theories that were considered relevant, such as the theory of Von Thunen, Weber and Christaller. From the spatial analysis process carried out, it can be seen that a strategic location in the formation of ULPs so that the range of services provided can meet the needs of the community.